Erlotinib plus tivantinib versus erlotinib alone in patients with previously treated stage IIIb/IV non–small-cell lung cancer: A meta-analysis based on randomized controlled trials. Issue 25 (19th June 2020) - Deng, Huan; Wang, Li; Chen, Xinling; Zhang, Shujuan; Yi, Fengming; Wei, Yiping; Zhang, Wenxiong
Abstract: Background: Whether erlotinib plus tivantinib (ET) can achieve better clinical benefits than erlotinib plus placebo (EP) among participants with previously treated advanced non-small-cell lung cancer (NSCLC) is still disputed. We conducted a meta-analysis to evaluate the anticancer efficacy and safety of both regimens. Materials and methods: We searched for pertinent trials at PubMed, ScienceDirect, The Cochrane Library, Scopus, Ovid MEDLINE, Embase, Web of Science, and Google Scholar. Endpoints mainly included progression-free survival (PFS), overall survival (OS), objective response rate (ORR), disease control rate (DCR), and adverse events (AEs). Results: We included 1522 patients who previously received ≥1 systemic anti-cancer regimen that included platinum-based chemotherapy. Although ET failed to improve OS (hazard ratio [HR] = 0.91, 95% confidence interval [CI]: 0.75–1.10, P = .35), the ET group had better PFS (HR = 0.73, 95% CI: 0.67–0.80, P < .00001), higher ORR (HR = 1.50, 95% CI: 1.06–2.12, P = .02), and better DCR (HR = 1.38, 95% CI: 1.20–1.59, P < .00001). Our subanalysis suggested that the ET group may have had better OS among patients with high Mesenchymal to epithelial transition factor (MET) expression (HR = 0.76, 95% CI: 0.58–0.99, P = .04) and good VeriStrat (HR = 0.88, 95% CI: 0.83–0.93, P < .0001). AEs were roughly similar except for specific hematological toxicities: more neutropenia and febrile neutropenia were observed in the ET group, both of which should not be overlooked. Conclusions: ET appears to be superior to EP due to better PFS and higher response rates, especially for patients with high MET expression and good VeriStrat. The greater hematological toxicity in the ET regimen is non-negligible. Abstract : Supplemental Digital Content is available in the text